Fibrinogen on Admission in Trauma score: Early prediction of low plasma fibrinogen concentrations in trauma patients. Issue 1 (January 2018) - Gauss, Tobias; Campion, Sébastien; Kerever, Sébastien; Eurin, Mathilde; Raux, Mathieu; Harrois, Anatole; Paugam-Burtz, Catherine; Hamada, Sophie
Abstract : BACKGROUND: Early recognition of low fibrinogen concentrations in trauma patients is crucial for timely haemostatic treatment and laboratory testing is too slow to inform decision-making. OBJECTIVE: To develop a simple clinical tool to predict low fibrinogen concentrations in trauma patients on arrival. DESIGN: Retrospective cohort study. SETTING: Three designated level 1 trauma centres in the Paris Region, from January 2011 to December 2013. PATIENTS: Patients admitted in accordance with national triage guidelines for major trauma and plasma fibrinogen concentration testing on admission. INTERVENTION: Construction of a clinical score [Fibrinogen on Admission in Trauma (FibAT) score] in a derivation cohort to predict fibrinogen plasma concentration 1.5 g l −1 or less after multiple regressions. One point was given for each predictive factor. The score was the sum of all. Validation was performed in a separate validation cohort. MAIN OUTCOME MEASURE: Predictive accuracy of FibAT score. RESULTS: In total, 2936 patients were included, 2124 in the derivation cohort and 812 in the validation cohort. In the derivation cohort, a multivariate logistic model identified the following predictive factors for plasma fibrinogen concentrations 1.5 g l −1 or less: age less than 33 years, prehospital heart rate more than 100 beats per minute, prehospital SBP less than 100 mmHg, blood lactate concentration on admission more than 2.5 mmol l −1, free intraabdominal fluid on sonography, decrease in haemoglobin concentration from prehospital to admission of more than 2 g dl −1, capillary haemoglobin concentration on admission less than 12 g dl −1 and temperature on admission less than 36°C. The FibAT score had an area under the receiver operating characteristic curve of 0.87 [95% confidence interval (0.86 to 0.91)] in the derivation cohort and of 0.82 (95% confidence interval (0.86 to 0.91)] in the validation cohort to predict a low plasma fibrinogen. CONCLUSION: The FibAT score accurately predicts plasma fibrinogen levels 1.5 g l −1 or less on admission in trauma patients. This easy-to-use score could allow early, goal-directed therapy to trauma patients.